Forward head posture is associated with pressure pain threshold and neck pain duration in university students with subclinical neck pain. (3rd April 2018) - Pacheco, Joana; Raimundo, João; Santos, Filipe; Ferreira, Mário; Lopes, Tiago; Ramos, Luis; Silva, Anabela G.
Abstract: Objective: The aims of this study are to investigate the association between: (i) forward head posture (FHP) and pressure pain thresholds (PPTs); (ii) FHP and maladaptive cognitive processes; and (iii) FHP and neck pain characteristics in university students with subclinical neck pain. Materials/methods: A total of 140 university students, 90 asymptomatic and 50 with subclinical neck pain, entered the study. Demographic data, anthropometric data, FHP, and PPTs were collected for both groups. In addition, pain characteristics, pain catastrophizing, and fear of movement were assessed for participants with neck pain. FHP was characterized by the angle between C7, the tragus of the ear, and the horizontal line. Correlation analysis and multivariate regression analysis were conducted. Results: Participants with subclinical neck pain showed significantly lower PPTs than participants without neck pain ( p < .05), but similar FHP ( p > .05). No significant association was found between FHP and PPTs in the asymptomatic group. In the group of participants with subclinical neck pain, PPTs at the right trapezius and neck pain duration explained 19% of the variance of FHP ( R 2 = 0.23; adjusted R 2 = 0.19; p < .05). Conclusion: This study suggests that FHP is not associated with PPTs in asymptomatic university students. In university students with subclinical neck pain, increased FHP was associated with right trapezius hypoalgesia and with neck pain of shorter duration. These findings are in contrast with current assumptions on the association between neck pain and FHP.